Strategi Pengelolaan BumDes di Pasar Terusan Kecamatan Muara Bulian Kabupaten Batang Hari Provinsi Jambi - Rury Rizki Handayani; Zulkipli Zulkipli; Robby Erviando; Eva Setiarini Damanik; Riman Abimayu; Elsya Fitrianisa (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
BumDes MANAGEMENT STRATEGY AT TERUSAN MARKET, MUARA BULIAN DISTRICT, BATANG HARI REGENCY, JAMBI PROVINCE.Village-Owned Enterprises (BUMDES) hold a strategic role in supporting village economic self-reliance; therefore, they require accountable and transparent financial management. BUMDes of Pasar Terusan Village still faces limitations in managers’ understanding of transaction recording and financial statement preparation. This community service activity aims to improve the financial management capabilities of BUMDes managers through the application of simple accounting. The methods used include training, mentoring, and hands-on practice in financial record-keeping. The materials cover the strategic role of BUMDes in village economic empowerment, professional and sustainable BUMDes management, as well as the stages of transaction recording and financial statement preparation. The results show an improvement in managers’ understanding of the accounting function and their ability to prepare simple financial statements in a more structured manner. This activity contributes to strengthening transparent and sustainable financial governance of BUMDes.